Commemorative plaque, Mother Teresa - Ghosh, Ayan (2023)
Commemorative plaques were placed on the pew, marking the visit by Mother Teresa on 8 January 1983. A second plaque was added to Mother Teresa's canonization at the Vatican City on 4 September 2016 by Pope Francis. Henceforth, Mother Teresa was known as Saint Teresa of Calcutta.